1985
DOI: 10.1111/j.1600-0714.1985.tb00510.x
|View full text |Cite
|
Sign up to set email alerts
|

Langerhans cell surface densities in rat oral mucosa and human buccal mucosa

Abstract: We determined surface densities of Langerhans cells (LCs) in rat oral mucosa and human buccal mucosa by enumerating ATPase‐positive dendritic cells in epithelial whole mounts. For the rat, mean surface densities per mm2 were 160 in anterior buccal mucosa, 640 in posterior buccal mucosa, 430 in the palate and 340 in the tongue. Human buccal mucosa showed a density of 890 cells per mm2. We conclude that LC densities in oral mucosa approximate those of external body sites, making them available in numbers suffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1

Year Published

1994
1994
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 31 publications
2
5
1
Order By: Relevance
“…The density of ATPase-positive LCs in non-irradiated specimens was 548∫144, which is within the range of LC densities reported in mucosal sites of different species (23)(24)(25). No difference was found in the density of LCs in the anterior and posterior parts of rat buccal OMM.…”
Section: Discussionsupporting
confidence: 76%
“…The density of ATPase-positive LCs in non-irradiated specimens was 548∫144, which is within the range of LC densities reported in mucosal sites of different species (23)(24)(25). No difference was found in the density of LCs in the anterior and posterior parts of rat buccal OMM.…”
Section: Discussionsupporting
confidence: 76%
“…DCs are thus phenotypically and functionally heterogeneous depending on their specific differentiation pathways (11,468,469). Serving as sentinels for pathogen entry at the epithelium of the skin and mucosa, Langerhans' cells, identified by expression of CD1a, Lag, and langerin, are localized on the basal and suprabasal layers and represent 2 to 4% of the cells in the epithelium (6,34,49,59,96,99,103,216,245,262,351,356,365,390,391,442 (30). The loose interaction of DC-specific, ICAM-3 grabbing, nonintegrin (DC-SIGN) with ICAM-3 establishes the initial contact of the Langerhans' cell with a resting T cell in the apparent absence of foreign antigen (416).…”
Section: Moreover Il-2 (But Not Gamma Interferon [Ifn-␥])-activated Cd8mentioning
confidence: 99%
“…Previous studies showed that epidermal LCs are antigen-presenting cells that interact with circulating T-lymphocytes (Streilein 1983). LCs were also reported to be present in the oral mucosa (Bos and Burkhardt 1980;Ahlfors et al 1985). Responses to external-applied antigen were observed to be similar in the skin and the oral mucosa (Ek et al1989;Bolewska and Reibel 1989).…”
Section: Discussionmentioning
confidence: 99%